Oleate Prevents Palmitate-Induced Mitochondrial Dysfunction in Chondrocytes - Vázquez-Mosquera, Maria Eugenia; Fernández-Moreno, Mercedes; Cortés-Pereira, Estefanía; Relaño, Sara; Dalmao-Fernández, Andrea; Ramos-Louro, Paula; Durán Sotuela, Alejandro; Rego-Pérez, Ignacio; Blanco, Francisco J. (Frontiers in Physiology, 2021)
The association between obesity and osteoarthritis in joints not subjected to mechanical overload, together with the relationship between osteoarthritis and metabolic syndrome, suggest that there are systemic factors related to metabolic disorders that are involved in the metabolic phenotype of osteoarthritis. The aim of this work is to study the effects of palmitate and oleate on cellular metabolism in an "in vitro" model of human chondrocytes. The TC28a2 chondrocyte cell line was used to analyze the effect of palmitate and oleate on mitochondrial and glycolytic function, ATP production and lipid droplets accumulation. Palmitate, but not oleate, produces mitochondrial dysfunction observed with a lower coupling efficiency, maximal respiration and spare respiratory capacity. Glycolytic function showed lower rates both glycolytic capacity and glycolytic reserve when cells were incubated with fatty acids. The production rate of total and mitochondrial ATP showed lower values in chondrocytes incubated with palmitic acid. The formation of lipid droplets increased in fatty acid conditions, being significantly higher when the cells were incubated with oleic acid. These results may help explain, at least in part, the close relationship of metabolic pathologies with OA, as well as help to elucidate some of the factors that can define a metabolic phenotype in OA.